Staphylococcus aureus peptidoglycan (PGN) induces pathogenic autoantibody production via autoreactive B cell receptor clonal selection, implications in systemic lupus erythematosus. Issue 131 (July 2022) - Ning, Wangbin; Cheng, Da; Howe, Philip H.; Bian, Chuanxiu; Kamen, Diane L.; Luo, Zhenwu; Fu, Xiaoyu; Ogunrinde, Elizabeth; Yang, Liuqing; Wang, Xu; Li, Quan-Zhen; Oates, Jim; et al.
Abstract: Objectives: There is an intricate interplay between the microbiome and the immune response impacting development of normal immunity and autoimmunity. However, we do not fully understand how the microbiome affects production of natural-like and pathogenic autoantibodies. Peptidoglycan (PGN) is a component of the bacterial cell wall which is highly antigenic. PGNs from different bacteria can differ in their immune regulatory activities. Methods: C57BL/6 and MRL/lpr mice were intraperitoneally injected with saline or PGN from Staphylococcus aureus or Bacillus subtilis . Spleen anti-double-stranded DNA (dsDNA) IgG + B cells were sorted for B-cell receptor sequencing. Serum autoantibody levels and kidney damage were analyzed. Further, the association between plasma S. aureus translocation and systemic lupus erythematosus (SLE) pathogenesis was assessed in women. Results: Administration of B. subtilis PGN induced natural-like anti-dsDNA autoantibodies (e.g., IgM, short lived IgG response, and no tissue damage), whereas S. aureus PGN induced pathogenic anti-dsDNA autoantibodies (e.g., prolonged IgG production, low IgM, autoantibody-mediated kidney damage) in C57BL/6 and/or MRL/lpr mice. However, serum total IgG did not differ. S. aureus PGN induced antibodies with reduced clonality and greater hypermutation of IGHV3-74 in splenic anti-dsDNA IgG + B cells from C57BL/6 mice. Further, S. aureus PGN promoted IgG class switch recombination via toll-like receptor 2. Plasma S. aureus DNA levels were increased in women with SLE versus control women and correlated with levels of lupus-related autoantibodies and renal involvement. Conclusions: S. aureus PGN induces pathogenic autoantibody production, whereas B. subtilis PGN drives production of natural nonpathogenic autoantibodies. Highlights: PGNs from S. aureus and Bacillus subtilis contribute to the production of pathogenic or nonpathogenic autoantibodies respectively. S. aureus PGN induces class switch recombination via TLR2; S. aureus PGN induces autoantibodies IgG anti-dsDNA with reduced clonality and greater hypermutation of IGHV3-74 in splenic anti-dsDNA IgG + B cells from C57BL/6 mice. Plasma S. aureus DNA levels were increased in women with SLE versus control women and correlated with levels of lupus-related autoantibodies and renal involvement.